Model Perilaku Brand Switching Konsumen Dalam Pembelian Produk Otomotif di Kota Medan - Nadia Ika Purnama (Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to determine how the Consumer Brand Switching Behavior Model in Purchasing Automotive Products in Medan City. This research is basic research. The population in this study were consumers of car owners in Medan City. The sampling technique is a non-probability sampling technique. The criteria used in the sampling are that the respondents of this study are consumers who own cars, have changed car brands in the last 3 years, and reside in Medan, while the sample is set at 145 people. Data collection techniques used were interviews (Interview) and a list of questions (Questionaire). The data analysis method used in this research is the Structural Equation Model method. The results showed that Brand Image has a positive and significant effect on satisfaction. Brand Image has a negative and significant effect on Brand Switching. Product quality has a positive and significant effect on satisfaction. Product quality has a negative and significant effect on Brand Switching. Satisfaction has a negative and significant effect on Brand Switching. Satisfaction can negatively mediate the effect of Brand Image on Brand Switching and Satisfaction can negatively mediate the effect of Product Quality on Brand Switching.